Applications for Systematic Smart Contracts on Blockchain - Elnara, Alvina Sevde; Morie Elvan, Beyza; Emine, Deniz Parisya; Saraswati, Fatin Annabeth (Blockchain Frontier Technology, 2023)
Although blockchain technology has recently attracted a lot of attention, there are still several technical challenges, such as security and scalability. This paper provides a comprehensive overview of blockchain applications and smart contracts, their primary issues, and appropriate solutions, and will assist to identify any gaps and future study. It also identifies the areas in which recent studies have concentrated. 292 papers were picked for the study from the best digital libraries. Only 28 publications were taken into consideration after a thorough review procedure using predetermined inclusion and exclusion criteria.